2003
DOI: 10.1207/s15327914nc4601_07
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cachexia and Tumor Growth Reduction in Walker 256 Tumor-Bearing Rats Supplemented With N-3 Polyunsaturated Fatty Acids for One Generation

Abstract: In this study we investigated the effect of lifelong supplementation of the diet with coconut oil (CO, rich in saturated fatty acids) or fish oil (FO, rich in n-3 polyunsaturated fatty acids, PUFAs) on tumor growth, animal survival, and metabolic indicators of cachexia in adult rats. Female Wistar rats were supplemented with CO or FO prior to mating and then throughout pregnancy and gestation, and then the male offspring were supplemented from weaning until 90 days of age. Then they were inoculated subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 37 publications
4
29
0
5
Order By: Relevance
“…Thus, dietary fish supplementation may have caused a reduction in plasma and/or whole blood viscosity that contributed to the decrease in renal vascular resistance. On the other hand, the control rats supplemented with fish oil had serum triacylglycerol and cholesterol levels similar to control animals (25). So, the lack of effect of this supplementation on renal function of control animals observed in the present study should be explained in part by the constancy of plasma lipid levels and in part by the little effect of inhibition of cyclooxygenase products on the renal parameters of normal rats and humans (3,4).…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…Thus, dietary fish supplementation may have caused a reduction in plasma and/or whole blood viscosity that contributed to the decrease in renal vascular resistance. On the other hand, the control rats supplemented with fish oil had serum triacylglycerol and cholesterol levels similar to control animals (25). So, the lack of effect of this supplementation on renal function of control animals observed in the present study should be explained in part by the constancy of plasma lipid levels and in part by the little effect of inhibition of cyclooxygenase products on the renal parameters of normal rats and humans (3,4).…”
Section: Discussionsupporting
confidence: 42%
“…Treatment with fish oil significantly reversed the reduction of food intake observed in the W rats, and reduced tumor growth rate. In a previous study by our group, we observed that several "cachectic" serum parameters such as glucose, lactate, cholesterol, and HDL-C returned to normal levels in WP rats (25). The mechanisms by which n-3 PUFAs combat neoplasmic cells are still unclear.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Plasma glucose, triacylglycerol (TAG), very low density lipoprotein (VLDL), low density lipoprotein (LDL) cholesterol, high density lipoprotein (HDL) cholesterol and total cholesterol (TC) concentrations were measured through colorimetric enzymatic assays as described by Togni et al 14 , 72-h after the last training section and at least 12 h fast. The results are expressed as mg/dL.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…Fatty acids were then extracted three times with 2 ml hexane. After the extraction procedure and saponification [24][25][26] the fatty acids were derivatized with 4-bromomethyl-7 methoxycoumarim [27], and the analysis performed on a Varian model LC-10A liquid chromatography. The samples were placed on a C8 column (25 cm × 4.6 mm i.d., 5 μm of particles), with a flow rate of 1 ml/min of acetonitrile/water (77:23, vol/vol), and a fluorescence detector (325 nm excitation and 395 nm emission).…”
Section: Determination Of Fatty Acids Content By Hplc and Alkylglycermentioning
confidence: 99%